Molecular Modelling of New Materials from the Tetrathiafulvalene Family - Abdelmalek, O.; Dibi, A.; Belaidi, S.; Gouasmia, A.; Kaboub, L. (Asian Journal of Chemistry, 2010)
The structural and electronic study of new molecular materials from the tetrathiafulvalene family were analyzed and compared by using molecular modelling (molecular mechanics, molecular dynamics, complete neglecting of differential overlapping and the extended Hückel theory. The good correlations between the calculated and experimental values are presented.